The Putative Type III Secreted Chlamydia abortus Virulence-Associated Protein CAB063 Targets Lamin and Induces Apoptosis - Marschall, Miriam Theresia; Simnacher, Ulrike; Walther, Paul; Essig, Andreas; Hagemann, Jürgen Benjamin (Frontiers in Microbiology, 2020)
Since intracellular survival of all chlamydiae depends on the manipulation of the host cell through type III secreted effector proteins, their characterization is crucial for the understanding of chlamydial pathogenesis. We functionally characterized the putative type III secreted C. abortus protein CAB063, describe its intracellular localization and identified pro- and eukaryotic binding partners. Based on an experimental infection model and plasmid transfections, we investigated the subcellular localization of CAB063 by immunofluorescence microscopy, immunoelectron microscopy, and Western blot analysis. Pro- and eukaryotic targets were identified by co-immunofluorescence, co-immunoprecipitation, and mass spectrometry. Transmission electron microscopy and flow cytometry were used for morphological and functional investigations on host cell apoptosis. CAB063 localized in the nuclear membrane of the host cell nucleus and we identified the chaperone HSP70 and lamin A as pro- and eukaryotic binding partners, respectively. CAB063-dependent morphological alterations of the host cell nucleus correlated with increased apoptosis rates of infected and CAB063-transfected cells. We provide evidence that CAB063 is a chaperone-folded type III secreted C. abortus virulence factor that binds lamin A thereby altering the host cell nuclear membrane structure. This process may be responsible for an increased apoptosis rate at the end of the chlamydial developmental cycle, at which CAB063 is physiologically expressed.